2022
DOI: 10.7759/cureus.21690
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Multidrug-Resistant Tuberculosis Affecting the Pleura

Abstract: The majority of cases with tuberculous pleuritis have negative acid-fast bacilli (AFB) on smear microscopy, making the diagnosis difficult. This case report is based on the successful diagnosis and management of an extra-pulmonary (EP) multidrug-resistant tuberculosis (MDR-TB) patient with a history of lymphoma. Initial tests revealed a right-sided pleural effusion and thickening of the pleura. The closed pleural biopsy, pleural fluid histopathology, culture, and drug sensitivity testing (DST) report revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…An interesting case was published in 2022, describing data on the successful use of Xpert MBT/Rif in a patient with multidrug-resistant tuberculosis to isoniazid and rifampicin, who had a right-sided pleural effusion and pleural thickening. Scientists confirmed that in all cases of exudative or lymphocytic pleural effusion, pleural biopsy samples of patients should be examined by the Xpert MBT/Rif method, cultural analyzes, and a genotypic sensitivity test for early diagnosis and successful patient management [29]. A comparison of the complex morphological study of pleural fluid biopsies and the molecular analysis of GeneXpert MBT/Rif pleural biopsies for the purpose of confirming the diagnosis of tuberculosis with other similar scientific studies of the early detection of MBT in patients with pleurisy showed high diagnostic efficiency of the Xpert MBT/Rif analysis.…”
Section: N Resultsmentioning
confidence: 99%
“…An interesting case was published in 2022, describing data on the successful use of Xpert MBT/Rif in a patient with multidrug-resistant tuberculosis to isoniazid and rifampicin, who had a right-sided pleural effusion and pleural thickening. Scientists confirmed that in all cases of exudative or lymphocytic pleural effusion, pleural biopsy samples of patients should be examined by the Xpert MBT/Rif method, cultural analyzes, and a genotypic sensitivity test for early diagnosis and successful patient management [29]. A comparison of the complex morphological study of pleural fluid biopsies and the molecular analysis of GeneXpert MBT/Rif pleural biopsies for the purpose of confirming the diagnosis of tuberculosis with other similar scientific studies of the early detection of MBT in patients with pleurisy showed high diagnostic efficiency of the Xpert MBT/Rif analysis.…”
Section: N Resultsmentioning
confidence: 99%
“…Diagnosing tuberculous pleural effusions is challenging as acid-fast bacilli (AFB) microscopy and culture commonly produce negative results in 48-96% of cases. More than 90% of patients have to undergo thoracocentesis, which is commonly used to detect a lymphocytic, exudative pleural effusion; in contrast, less than 10% of patients undergo direct examination to detect AFB [ 3 ]. We need alternative diagnostic approaches as AFB staining and culture usually yield negative results.…”
Section: Introductionmentioning
confidence: 99%